A framework for categorizing the interactions of offshore windfarms and fisheries. (7th July 2022) - Stokesbury, Kevin D E; Fay, Gavin; Griffin, Robert
Abstract: The offshore windfarm industry has great potential for sustainable energy but requires space. The ability of fisheries to harvest within these windfarms varies. This has created a conflict between these two industries and discussions are hampered by differing approaches to the marine environment, a lack of understanding of what each industries requires, the significant money at stake, and the values the public place on marine conservation. To characterize, standardize, and quantify the scientific data addressing these concerns requires a framework. The framework should categorize data on spatial scales of 1 cm 2 to 1 km 2 (individual turbines/fishing vessels), 1–1000 km 2 (companies), and >1000 km 2 (regions), and by their ecological, economic, cultural, and institutional impacts. The framework should be repeated over temporal scales of the windfarm: pre-development (1–3 years), construction (1–2 years), post-construction (20–40 years), and decommission. Balancing the metrics used to describe the two industries will allow people to communicate clearly in an organized systematic way, hopefully resulting in a continuing supply of sustainable sea food and renewable energy to an increasingly hungry world.